A Measurement Scale for School Leadership Professional Development Needs for the Fourth Industrial Revolution - Omotayo A. Awodiji; Suraiya R. Naicker (E-Journal of Humanities, Arts and Social Sciences)
Research has shown that school leaders must improve their knowledge and skills as the Fourth Industrial Revolution (4IR) dawns. Thus, the study validated a scale that could be adopted to assess school leaders’ development needs in the 4IR. Specifically, this study estimated the instrument’s validity, determined the number of factors underlining the scale, and established the reliability coefficient of the scale. A quantitative survey design was used. A systematic sampling was conducted to select 284 respondents from selected basic schools (public and private) in the Ibadan metropolis, Oyo State, Nigeria. A content validity ratio (CVR) and a content validity index (CVI) were calculated based on the judgments of the panelists. Using Ordinal, Omega, and Guttmann Alpha approaches, statistical computing was done using R software (R Core Team, 2020) to determine the underlying factors of the scale items using exploratory factor analysis (EFA). A parallel analysis identified eight factors: school leaders’ knowledge of 4IR attributes, leaders’ technology needs, easy usage of basic technology applications, agility, information management and evaluation, communication expressiveness and collaboration, critical thinking and problem-solving, and creativity. Based on the results, the scale is valid for measuring the construct, showing good content and construct validity. Also, there was high internal consistency in all the approaches used. The scale is reliable and valid. The study recommends that school leaders, administrators, researchers, and other stakeholders adopt this scale to assess their skills development needs in the 4IR era. Hence, scholars could use the scale to conduct reliable studies in Nigeria and other Sub-Saharan African nations.